2019
DOI: 10.1089/jop.2018.0101
|View full text |Cite
|
Sign up to set email alerts
|

Novel Triamcinolone Acetonide-Loaded Liposomes Topical Formulation for the Treatment of Cystoid Macular Edema After Cataract Surgery: A Pilot Study

Abstract: Purpose: To report tolerability, safety, and efficacy of a topical triamcinolone acetonide-loaded liposomes formulation (TA-LF) in targeting the macular area in patients with refractory pseudophakic cystoid macular edema (PCME). Methods: For tolerability, safety and efficacy evaluation, 12 eyes of 12 patients with refractory PCME were exposed to one drop of TA-LF (TA at 0.2%) every 2 h for 90 days or until best-corrected visual acuity (BCVA) was achieved. Intraocular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 61 publications
3
23
0
2
Order By: Relevance
“…26 Finally, multiple efforts have been made to generate a topical formulation for the delivery of TA into the posterior segment of the eye using different delivery strategies such as those that include liposomes and lipid nanoparticles 26,28,72,73 ; however, only TA-LF has been proved in clinical assays, where its efficiency and safety profiles have satisfactorily been demonstrated. 27 Once again, in this study, we observed that TA-LF is well tolerated and holds an acceptable safety profile, with no ocular AEs.…”
Section: Triamcinolone Acetonide-loaded Liposomes After Flacssupporting
confidence: 59%
See 3 more Smart Citations
“…26 Finally, multiple efforts have been made to generate a topical formulation for the delivery of TA into the posterior segment of the eye using different delivery strategies such as those that include liposomes and lipid nanoparticles 26,28,72,73 ; however, only TA-LF has been proved in clinical assays, where its efficiency and safety profiles have satisfactorily been demonstrated. 27 Once again, in this study, we observed that TA-LF is well tolerated and holds an acceptable safety profile, with no ocular AEs.…”
Section: Triamcinolone Acetonide-loaded Liposomes After Flacssupporting
confidence: 59%
“…In synthesis, TA-LF has proved to deliver TA into the vitreous cavity and the retina, evading ocular barriers. 26 Moreover, it has been demonstrated that this formulation is efficient in the management of refractory PCME, 27 and, as our results have already shown, it is also useful in the prophylactic treatment of PCME without inducing a rise in IOP or the appearance of side effects.…”
Section: Triamcinolone Acetonide-loaded Liposomes After Flacsmentioning
confidence: 53%
See 2 more Smart Citations
“…In refractory PCME cases, the use of bevacizumab reduced macular thickness and improved BCVA in retrospective and prospective non-comparative studies [36]. In addition, in PCME topical triamcinolone-liposomes [37], interferon alpha 2b [38], interferon alpha 2a taken systemically [39], and the use of intravitreal infliximab [40] showed promising anatomical and functional responses to the treatment. To avoid overtreatment, based on the results presented here, we do not recommend the routine use of intravitreal or periocular injective treatments, nor systemic drug administration.…”
Section: Discussionmentioning
confidence: 99%